Inhibition of kappa opioid receptor (KOR) augments ketamine anti-depressive properties in the mouse model of depression - Živanović, Ana; Mitić, Miloš; Lukić, Iva; Adžić , Miroslav; Ivković, Sanja (Archives of Pharmacy, 2022)
Major depressive disorder (MDD) is one of the most prevalent and debilitating mental disorders affecting over 300 million people. Classical antidepressants have a slow onset of their therapeutic effects and are not effective in about 30% of MDD patients. Ketamine emerged as a novel and highly effective anti-depressant drug. However, the effects of ketamine are transient and may involve the unwanted side effects. Thus, the enhancement of ketamine-based anti-depressive therapies is essential. The opioid signalization can modulate ketamine antidepressant actions, and, the focus was given to kappa opioid receptor (KOR) as it was shown that its inhibition can also exert antidepressive effects. Ketamine is a non-competitive NMDAR antagonist acting through the mTORC1 signaling, while the KOR antagonists (such as norbinaltorphimine, NorBNI) induce the activation of c-Jun N-terminal Kinase (JNK). In this study, combined ketamine/NorBNI treatment prolonged anti-depressive-like behavior in adult male mice in the animal stress model of depression. The combined treatment increased the activation of mTOR signaling in the striatum, one of the brain structures affected in depression. In the same time ketamine/NorBNI decreased the activation of JNK confirming the dominant inhibitory effect of ketamine on JNK activation. These molecular alterations could be responsible for the prolonged anti-depressant effect of the ket+NorBNI treatment. Our results strongly suggest that simultaneous modulation of glutamate and opioid signaling can prolong the anti-depressive effects of ketamine in male mice. Therefore, NorBNI can be considered as a possible adjuvant in the ketamine anti-depressant treatment, at least in males.